Update Gynecologic Malignancies 2025 – Expert Opinion on Systemic Therapy for Early and Advanced Gynecological Cancers - Emons, Julius; Gocke, Julia; Schulmeyer, Carla; Stübs, Frederik Alexander; Krückel, Annika; Amann, Niklas; Beckmann, Matthias W.; Hörner, Manuel; Pöschke, Patrik (Geburtshilfe und Frauenheilkunde, 2025)
There have been major changes in the understanding of gynecologic malignancies in recent years, leading to new therapy options and subsequently to greater responsibilities for every professional treating those patients. The most significant therapeutic advances were achieved with checkpoint inhibitors (CPI), especially for endometrial and cervical cancer. In ovarian cancer the dominant and most important new substances are poly (ADP-ribose) polymerase inhibitors (PARPi). This review aims to summarize the latest studies and developments in the therapeutic landscape of endometrial, ovarian, and cervical cancer. The treatment of advanced endometrial cancer has changed significantly with the introduction of CPI such as dostarlimab (RUBY trial), durvalumab (DUO-E trial) and pembrolizumab (Keynote-868 trial). For ovarian cancer PARPi have shown substantial PFS benefits in key approval trials, including PRIMA for niraparib, PAOLA for olaparib, and ATHENA-MONO for rucaparib. These findings have established PARPi as the standard of care in maintenance therapy. Overall survival (OS) data for PRIMA and PAOLA are now available and are analyzed and placed into context in this article. Furthermore, mirvetuximab soravtansine is the first antibody-drug conjugate (ADC) approved in Germany for platinum-resistant ovarian cancer for patients with folate receptor alpha expression. The Keynote-A18 and BEATcc trials have opened new options for the utilization of immuno-oncology in cervical cancer treatment. Along with new therapeutic options, new biomarkers have also become part of daily clinical practice as predictive and prognostic factors as well as forming the basis for targeted personalized medicine.The use of CPI is revolutionizing the treatment of all gynecologic cancers and offers significant benefits for progression-free survival (PFS) and OS in most therapy regimens. With the increased use of ADCs, this is not the end of these developments. Therapy algorithms from a certified German oncology center are developed and presented in this article.
Keywords: gynecologic malignancies; endometrial cancer; ovarian cancer; cervical cancer; immune oncology